FISHES OF THE ESTUARIES OF MIMIKA DISTRICT, PAPUA PROVINCE - Haris, Abdul; Lala, Deky; Setyadi, Gesang (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2008)
Study on estuarine fishes in Mimika district, Papua was carried out at six estuaries from 2000 to 2006, as a part of monitoring program conducted by PT Freeport-Indonesia. This study mainly aimed to document the fish diversity, dominance, abundance and weight. Samples were collected from six estuaries, namely Ajkwa (tailing affected estuary), Tipoeka (disturbed estuary), Minajerwi, Kamora, Mawati and Otakwa (tailings unaffected estuaries). The total fish catches from the study sites during the study were 133 species belonging to 50 families, with the total abundance and wet weight were 85,523 individuals and 1,834 kg, respectively. The indices of diversity and evenness ranged 1.1-2.1 and 0.4-0.8, respectively. Based on the sample abundance, the dominant families consisted of pony fishes (Leiognathidae), drum fishes (Sciaenidae) and anchovies (Engraulidae), catfish (Ariidae) and glassfish (Ambassidae), whereas based on the samples weight, the dominant families comprised of Sciaenidae, Ariidae, Leiognathidae, Engraulidae and Clupeidae. The results show that there were no significantly differences in diver-sities and abundances among the six estuaries of Mimika district.